DETERMINANTS AFFECTING FINANCING MURABAHAH AT SYARIAH COMMERCIAL BANKS IN INDONESIA 2016-2020 PERIOD - Fatrilia Rasyi Radita; Sri Wahyuni Asnaini; Siti Maesaroh (Journal Of Communication Education, 2022)
Islamic banks, like conventional banks, have a function as financial intermediaries, having the main task of collecting funds from the public and channeling them back to the community in the form of financing facilities. The basic difference between the two banks is that Islamic banks carry out their business activities not based on interest (interest fees), but based on sharia principles or the profit and loss sharing principle. Murābahah is Islamic bank financing through a buying and selling system for or services with a profit agreement and a certain period of time. The purpose of this study was to analyze the determinants of Murabahah financing seen from microeconomic factors such as Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (BOPO) as well as from macroeconomic factors such as Bank Indonesia Syariah Certificates (SBIS), BI rate and inflation. The data that has been collected was analyzed using multiple regression analysis. The results obtained from this study show that the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), BI Rate and inflation have a significant effect on Murabahah financing. Meanwhile, Return on Assets (ROA), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (BOPO) and Bank Indonesia Syariah Certificates (SBIS) have no significant effect on Murabahah financing. Keywords: Murabahah Financing, Microeconomic Factors, Macroeconomic Factors